Shear Strengthening of RC Beams Using Partial-Length Near-Surface Mounted (PLNSM) CFRP Strips - Khol, Senghong; Seo, Soo-Yeon; Van Tran, Hai; Hanif, Muhammad Usman (International journal of concrete structures and materials, 2024)
Shear strengthening of reinforced concrete beams using near-surface mounting (NSM) method with fiber-reinforced polymer (FRP) strips is more effective because of improved bond strength, better fire resistance and high maintainability. However, the surface preparation for NSM method is a difficult process where the beam–slab corner is not accessible by the rotary blade of the groove-making equipment. Consequently, the application of NSM method becomes more difficult to apply. Therefore, in this study, the effect of reducing in NSM length on the shear strength has been investigated by reinforcing only a part of the height, not the entire web of beam, referred to as the partial-length NSM method (PLNSM). Half scaled five RC T-beams were made and tested under symmetrical four-point static loading system. All except one was strengthened in shear in which the effect of reduced NSM length was balanced by inclining the partial-length NSM strips (IPLNSM). Furthermore, to mitigate the detrimental effect of reduced lengths of NSM strips, the retrofitting was enhanced by additional externally bonded reinforcement (EBR) method using CFRP sheets. The results showed that there was no significant negative effect of reduced NSM length on the strength of the strengthened specimens, and by providing inclined NSM strips, significant improvement in the strength was observed. Additionally, the hybrid approach combining the inclined partial length NSM (IPLNSM) and EBR method showed improvement in strength and deflection capacity. Lastly, when compared with the currently available design procedures, it was found that the available formulation can predict the design strength of PLNSM and IPLNSM reinforcement, thus making them a viable option for retrofitting reinforced concrete beams.